Microcrystalline testing used in combination with Raman micro‐spectroscopy for absolute identification of novel psychoactive substances. (30th May 2016) - Elie, Leonie; Elie, Mathieu; Cave, Gareth; Vetter, Marleen; Croxton, Ruth; Baron, Mark
Abstract : Two new psychoactive substances, namely 4‐methylmethcathinone (mephedrone) and 5, 6‐methylenedioxy‐2‐aminoindane (MDAI) were analysed with a novel combination of microcrystalline tests followed by Raman micro‐spectroscopy to facilitate their absolute identification. The discrimination power of the proposed combination was successfully demonstrated through the analysis of the positional isomers 2‐ and 3‐methylmethcathinone. The addition of mercury dichloride as a microcrystalline test reagent produced specific microcrystals of each tested analyte. The robustness of the method was evaluated in the presence of common cutting agents (caffeine and benzocaine) as well as on street samples. The crystal lattice structures of mephedrone, 2‐methylmethcathinone and MDAI mercury dichloride microcrystals were determined by single crystal X‐ray diffraction. This confirmed the presence of both drug and reagent together in the lattice and accounts for the distinct habit of the observed microcrystals. Raman spectra of the formed microcrystals differed from those obtained from their standard salt form by loss and/or gain of some vibrational modes. Particularly important was the appearance of the mercury chloride link to each tested drug molecule which showed as strong bands at low wavenumbers. Its presence was corroborated by its detection in the crystal lattice. It was therefore concluded that microcrystalline testing followed by Raman micro‐spectroscopy satisfies the technique combination requirement for psychoactive substances recommended by the Scientific Working Group for the Analysis of Seized Drugs (SWGDRUG) and provides a rapid and cheap analysis route. The proposed technique combination also aids the development of new microcrystalline tests as it allows for confirmation of the uniqueness of the developed microcrystals almost in‐situ rather than growing single crystals for often long periods of time needed for single crystal X‐ray diffraction analysis. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A combination of microcrystalline testing and Raman micro‐spectroscopy is presented as an analytical strategy for absolute identification of new psychoactive substances. This approach bypasses the need of crystal elucidation by X‐ray diffraction, is quick to perform and simple to set up for the routine analysis of street drugs while fulfilling all SWGDRUG criteria.